A Systematic Review on Immunotherapy for Guillain- Barre Syndrome (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Guillain-Barré syndrome (GBS) is an acute immunemediated polyradiculoneuropathy with a highly variable clinical course and outcome. Intravenous immunoglobulin (IVIG) and plasma exchange (PE) are proven effective treatments, but about half of the patients may not respond to these therapies; moreover, these are not established yet to treat patients of every stage of GBS or its variants. Results from the International Guillain-Barré Syndrome Outcome Study suggest that geographical variations exist in Guillain-Barré syndrome, including insufficient access to immunotherapy in low-income countries. There is a need to provide improved access to treatment for all patients with Guillain-Barré syndrome, and to develop effective disease-modifying therapies that can limit the extent of nerve injury. In this review, the current literature about immunotherapeutic options is highlighted in the context of stages of the disease and its variants and additionally, upcoming modalities are discussed briefly.J Bangladesh Coll Phys Surg 2022; 40: 57-64